Aging Sexual Knowledge and Attitude Scale: Turkish Validity and Reliability Study - Hasan Anıl Kurt; Cabir Alan; Büşra Yılmaz; Handan Alan (Journal of Contemporary Medicine, 2022)
Objectives: It is designed to test the Turkish version of ASKAS's validity and reliability for use with older people, health professionals, and people who influence older people. Material and Method: Language and content validity, item analysis, exploratory and confirmatory factor analysis, and internal consistency coefficients were evaluated in this study. Results: It was decided to omit two items from the scale's knowledge subscale, and the three-factor structure of the attitude subscale was found to be within the range of acceptable fit indices. Conclusions: The Turkish version of ASKAS was determined to be valid, reliable, and applicable in practice.